WILSON’S DISEASE - A. Hancu (Romanian Journal of Neurology, 2011)
A disturbance of copper metabolism causes hepatolenticular degeneration (Wilson’s disease), an autosomal recessive disorder whose genetic locus lies on the long arm of chromosome 13. The concentration of the copper transport protein ceruloplasmin is abnormally low and, as a result, the serum free copper concentration is high and an abnormally large amount of copper is eliminated in the urine. Free copper is deposited in the liver, the edge of the cornea, the brain. We present a case who debuted by tremors and thrombocytopenia. Continuous therapy with Trientine hydrochloride and Mega zinc, and elimination of copper rich foods were improved cognitive, behavioral and motor dysfunctions.